Development of microparticles containing polylactic acid/bioactive glass/caffeic acid - ULAĞ, SONGÜL (My University, 2023)
Bone diseases or defects cause significant problems for people around the world, both in terms of the economy and their health. The deficiencies in traditional methods have led researchers to focus on bone tissue engineering (BTE) and explore new and improved methods. In this study, the production and characterization of microparticles (MPs) for BTE are emphasized. By using the polylactic acid (PLA), bioactive glass (BG), and caffeic acid (CA) electrospray (ES) method with optimum parameters, four different types of MPs (3% PLA, 3% PLA/0.1% BGs, 3% PLA/0.1% CA, and 3% PLA/0.1% BGs/0.1% CA) were produced. Scanning electron microscopy (SEM) analysis revealed an increase in the mean diameter with the addition of substances. Fourier transform infrared spectroscopy (FTIR) analysis confirmed the presence of the main material, PLA. Differential scanning calorimetry (DSC) analysis demonstrated that the added substances affected the thermal properties of PLA. X-ray diffraction (XRD) analysis showed that the substances had minimal impact on the PLA pattern. In addition, in the in vitro drug release test, the release characteristics of CA from MPs were examined, and as a result, different compositions at different rates (180 min and 720 min) were determined. Moreover, the 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay results showed that the MPs did not show toxicity against human fetal osteoblastic (hFOB) 1.19 cell lines. In conclusion, this study provides comprehensive information about the production and characterization of MPs and will be a promising study for use in BTE studies thanks to the results obtained.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)